2018
DOI: 10.18203/issn.2455-4510.intjresorthop20181809
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of patients undergoing lumbar discectomy

Abstract: <p class="abstract"><strong>Background:</strong> Sciatica resulting from a lumbar intervertebral disc herniation is the most common cause of radicular leg pain in adult working population. It can be treated with both conservative and operative methods. In our study, surgical treatment of lumbar disc prolapse has been done by open discectomy. We wish to assess the outcome of surgery in patients with lumbar disc prolapse undergoing lumbar discectomy.</p><p class="abstract"><stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
4
3
0
Order By: Relevance
“…It was observed in the present study that majority of the patients (73.3%) presented with protrusion. This is similar to the study of Singh H et al 6 Who found protrusion in 82.5% patients on MRI. In our study, 3 (10%) patients had complications -2 (6.7%) patients had superficial surgical site infection and 1 (3.3%) patient had dural tear.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It was observed in the present study that majority of the patients (73.3%) presented with protrusion. This is similar to the study of Singh H et al 6 Who found protrusion in 82.5% patients on MRI. In our study, 3 (10%) patients had complications -2 (6.7%) patients had superficial surgical site infection and 1 (3.3%) patient had dural tear.…”
Section: Discussionsupporting
confidence: 92%
“…It was observed in the present study that left side was mostly involved (43.3%) followed by right side radiculopathy (36.7%) and bilateral involvement (20%). This is concordant to the study of Singh H et al 6 in which left side was most commonly involved (42.5%). The commonest level of disc prolapse in our study was found to be L4-5 (80%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Swamy A et al (7) conducted a study on 50 patients of which 4 (8%) patients had prolapsed intervertebral disc at L2-L3 level and 10 (20%) patients had disc prolapsed at L3-L4 level, 22 (44%) patients had disc prolapsed at L4-L5 level and 14 (28%) patients had disc prolapsed at L5-S1 level. Singh H et al 6 in their prospective study observed L4-5 level was most commonly involved level (72.5%). Mittal A et al 5 randomised prospective analysis observed commonest level of disc prolapse was found to be L-4-L5 (80.5%).…”
Section: Discussionmentioning
confidence: 91%